2017
DOI: 10.1097/igc.0000000000000952
|View full text |Cite|
|
Sign up to set email alerts
|

A New Diagnostic and Prognostic Marker in Endometrial Cancer: Neopterin

Abstract: This study suggests that urinary neopterin levels are relevant in evaluating the endometrial cancer stage and follow-up of the disease. As a result, using neopterin and cancer antigen 125 together would be useful in determining the prognosis of endometrial cancer and its posttreatment progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The human gene expression 4× 44 K v2 Microarray (Agilent Technologies, Santa Clara, CA, USA) was used for the experiments. Sample labeling and array hybridization were performed according to the Agilent One-Color Microarray-Based Gene Expression Analysis protocol (Arraystar Inc., Rockville, MD, USA) [ 44 ]. Labeled cRNA (1 μg) was fragmented by adding a 10× Blocking Agent (11 μL) and a 25× Fragmentation Buffer (2.2 μL); it was then heated at 60 °C for 30 min, and finally, the labeled cRNA was diluted with a 2× GE Hybridization buffer (55 μL).…”
Section: Methodsmentioning
confidence: 99%
“…The human gene expression 4× 44 K v2 Microarray (Agilent Technologies, Santa Clara, CA, USA) was used for the experiments. Sample labeling and array hybridization were performed according to the Agilent One-Color Microarray-Based Gene Expression Analysis protocol (Arraystar Inc., Rockville, MD, USA) [ 44 ]. Labeled cRNA (1 μg) was fragmented by adding a 10× Blocking Agent (11 μL) and a 25× Fragmentation Buffer (2.2 μL); it was then heated at 60 °C for 30 min, and finally, the labeled cRNA was diluted with a 2× GE Hybridization buffer (55 μL).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, 2-DE is a time consuming technique with limited sample throughput and narrow depth of proteome analysis. Bostanci and colleagues used high performance liquid chromatography to compare urine samples from 41 EC cases and 41 healthy controls and found neopterin to be differentially expressed (55). Neopterin, a marker of cellular immune Age related changes in urinary protein excretion.…”
Section: Urinary Proteins and Peptidesmentioning
confidence: 99%
“…Co-variant analysis activation, was also able to differentiate early from late stage disease, suggesting a potential prognostic use especially if it is found to be a specific marker of EC and not an inflammatory response marker. The positive predictive value of neopterin is poor, however, as elevated levels may also be found in autoimmune conditions, viral and bacterial infections and other malignant states (55). In the study by Stockley and colleagues, urine sediment MCM5 discriminated EC cases (n = 41) from benign gynecological disease (n = 58) with an AUC of 0.83.…”
Section: Not Applicablementioning
confidence: 99%
“…Ratio of kynurenine to tryptophan (KTR) and neopterin, a metabolite of guanosine triphosphate, are markers of interferon (IFN)-gamma-induced immune activation [ 14 ]. Although some studies reported that KTR and neopterin were associated with increased risk of several cancers and all-cause mortality [ 15 19 ], their association with risk of pancreatic cancer has not been investigated.…”
Section: Introductionmentioning
confidence: 99%